Pelatihan Keterampilan Bahasa Arab Dasar pada Siswa Kelas 6 SD Islam Kendari Melalui Penggunaan Kitab Al-Arabia Lil Kibar - Yusril; Wa Muna (Jurnal Abdimas Nusantara, 2024)
Kendari Islamic Elementary School is one of the private schools supported by the Islamic Education Foundation and is located in the district. West Kendari Kel. Watu-watu, Kendari City, Southeast Sulawesi. Basic Arabic Language Training at the Kendari Islamic Elementary School is carried out over four meetings or 4 days, namely Monday to Tuesday, the estimated time for each meeting is one hour to one and a half hours. The training learning process is carried out from 10:00 – 11:30. This training is to provide an understanding of basic Arabic language muhadatsa, the methods in this basic Arabic language training are communicative methods and vocabulary methods. The implementation of this basic Arabic language training program was carried out at the Islamic Elementary School under the auspices of the Kendari Islamic Education Foundation and the Ministry of Education and Culture, involving grade 6 students at the Kendari Islamic Elementary School as the subjects of this service. This service is carried out consecutively for four days. Based on the results of the Basic Arabic language training using the Al-Arabia Lil Kibar book, it can be concluded that this training can increase insight into basic Arabic muhadatsa at the Kendari Islamic Elementary School